2021
DOI: 10.1002/ange.202100345
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing Aptamers Block S/RBD‐ACE2 Interactions and Prevent Host Cell Infection

Abstract: The receptor-binding domain (RBD) of the severe acute respiratory syndrome coronavirus 2s pike (S) protein playsacentral role in mediating the first step of virus infection to cause disease:v irus binding to angiotensin-converting enzyme 2( ACE2) receptors on human host cells.T herefore, S/RBD is an ideal target for blocking and neutralization therapies to prevent and treat coronavirus disease 2019 (COVID-19). Using at arget-based selection approach, we developed oligonucleotide aptamers containing ac onserved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 33 publications
0
39
0
Order By: Relevance
“…Several other DNA aptamers have been selected to bind the receptor binding domain (RBD) ( 17 , 20 ), the S1 protein ( 21 ), trimerized S1 protein ( 19 ), and virus mimics ( 18 ). We performed a BLAST ( 55 ) comparison of our top 10 aptamers with these aptamers and found our aptamers to be distinct from all other published aptamers surveyed ( Supplementary Figure S13A ).…”
Section: Discussionmentioning
confidence: 99%
“…Several other DNA aptamers have been selected to bind the receptor binding domain (RBD) ( 17 , 20 ), the S1 protein ( 21 ), trimerized S1 protein ( 19 ), and virus mimics ( 18 ). We performed a BLAST ( 55 ) comparison of our top 10 aptamers with these aptamers and found our aptamers to be distinct from all other published aptamers surveyed ( Supplementary Figure S13A ).…”
Section: Discussionmentioning
confidence: 99%
“…We developed SARS-CoV-2-specific DNA aptamers as well. Our functional study reveals that t binds to either S or the receptor-binding domain (RBD) with high affinity (K d = 6.05 nM) (Figure 5 ) 67 . Furthermore, our findings indicate that the aptamer can be used to detect living viral particles, using ddPCR technology (the detection method is establishing).…”
Section: Potential Utility Of Aptamer Technology For Pathogen Detectionmentioning
confidence: 92%
“…They finally identified one S protein-targeted aptamer that could inhibit the SARS-CoV-2 pseudo-virus cell entry through an RBD-ACE2 interaction-independent way, though this aptamer held a strong binding affinity to S protein (K d = 13.9 nM). We have developed an RBD-specific DNA aptamer using RBD protein-SELEX with a strong binding affinity (K d = 6.05 nM) and found that the aptamer neutralized both pseudo- and authentic SARS-CoV-2 virus and efficiently prevented human host cell infection in vitro (Figure 7 ) 67 . Most recently, Yang et al developed six DNA aptamers using capillary electrophoresis-based SELEX 254 .…”
Section: Potential For Aptamer Technology In Communicable Disease Therapeuticsmentioning
confidence: 99%
“…COVID-19 has wreaked havoc all over the world, but no specific treatment has been developed yet. Liu and his colleague developed an aptamer that specifically targets the spike protein of the coronavirus SARS-CoV-2, which is the critical role of viral infection ( Liu et al, 2021 ). When the receptor-binding domain (RBD) of the spike protein of the coronavirus SARS-CoV-2 binds to the human angiotensin-converting enzyme 2 (ACE2), an infection cascade is triggered ( Schmitz et al, 2021 ).…”
Section: Application Of Aptamers In Infectious Diseases Treatmentmentioning
confidence: 99%